MECHANICAL RESPONSE OF LINED AND UNLINED HEATED DRIFTS - Elsworth D. (My University, 2001)
Approximate relations are developed to determine the steady stresses and displacements that may develop in unlined and lined drifts heated above ambient, as representative of conditions in a nuclear waste repository. For a series of parallel, unlined drifts, radial convergence due solely to thermal effects is everywhere at early-times; at late times it is a maximum inward at springline, and an equivalent maximum outward at crown and invert. Support pressures and hoop stresses are evaluated for a flexible liner placed in intimate contact with the drift wall, following excavation, where a full slip condition is applied at the drift-liner interface. For rock mass moduli of similar order to, or smaller than, the liner modulus, hoop stresses and support pressures are shown insensitive to rock mass parameters. Surprisingly, liner stresses are strongly controlled by liner modulus, liner Poisson ratio, liner thermal expansion coefficient, and instantaneous liner temperature, and only weakly by rock mass modulus. Response is shown independent of thermal expansion coefficient of the rock mass, and temperature distribution beyond the drift wall. The "misfit" expansion of the liner in the drift cavity controls liner stresses that rise linearly with the temperature of the liner, alone. Importantly, the results demonstrate the potential to control magnitudes of thermal stresses by the incorporation of compressible elements within the liner, or within the blocking or backfill behind the liner. Although the results are partly conditioned by the assumptions of a fully flexible liner and full slip conditions at the drift-liner interface, they serve to define the important parametric dependencies in the mechanical response of heated drifts.